A Search for Radio Millisecond Pulsar Companions around Extremely Low-mass White Dwarfs with Ellipsoidal Variability - W. J. Huang; Pak-Hin Thomas Tam; L. L. Ren; J. M. Lin (The Astrophysical Journal)
Extremely low-mass (ELM) white dwarfs (WDs) are helium-core WDs with masses less than 0.3 M _⊙ . Short-period ELM WD binaries that exhibit ellipsoidal variations may harbor heavier companions, either massive WDs or millisecond pulsars (MSPs). In this study, we selected ∼12,000 ELM WDs or their candidates, and searched for ellipsoidal-like lightcurves with orbital periods shorter than 1 day, by using the public data from Zwicky Transient Facility. Finally, 23 such systems were found, with 17 being newly discovered. We selected nine high-priority targets likely to evolve from the Roche lobe overflow channel and estimated their companion masses from the extracted ellipsoidal variation amplitude. Among them, four targets have companion masses exceeding 1 M _⊙ . We performed a search for radio pulsations from six of these targets by using Five-hundred-meter Aperture Spherical radio Telescope. However, no convincing radio pulse signals were found, resulting in upper limits for the radio flux at around 8 μ Jy. Given the nondetection of radio pulsations from a total of 11 similar systems, the fraction of ellipsoidal ELM WDs around MSPs is estimated to be below 15 ${}_{-3}^{+6}$ %. We anticipate that multiwavelength studies of more ellipsoidal-like ELM WDs will further constrain the fraction.